A systematic review of the presentation of scan-negative suspected cauda equina syndrome. Issue 1 (February 2020) - McDonnell, Jake; Ahern, Daniel P.; Gibbons, Denys; Dalton, David M.; Butler, Joseph S.
Abstract: Background: A significant proportion of patients presenting with suspected cauda equina syndrome (CES) do not have associated radiological evidence to support the diagnosis, often termed 'scan-negative'. Due to the limited number of studies regarding the matter, there is no clear understanding for this presentation. As a result, no treatment protocol exists for the scan-negative group. The purpose of this review is to assess the potential contributing factors leading to the presentation of suspected CES with normal imaging. Methods: A systematic review was conducted on PubMed and Cochrane databases. Bibliographies of key articles and Google Scholar were searched for additional results. The search strategy provided 204 results. Of those, 8 had no identifiable causation for suspected CES and were included for systematic review. Results: 6 of 8 studies investigated for a difference in clinical presentation between cohorts that may indicate a normal scan. Studies were either inconclusive and contradictory. Two studies suggest a functional somatic disorder as reasoning for negative MRI, with positive provisional findings. Conclusion: A psychogenic hypothesis is plausible and warrants further investigation. The need for additional studies is essential to scheming a potential treatment protocol for the scan-negative population, which currently does not exist. Highlights: Cauda Equina Syndrome (CES) is an acknowledged medical emergency. A notable percentage of patients with clinically suspected CES have normal radiological imaging. No treatment protocol currently exists for such a population. There are no defining clinical characteristics that aid in distinguishing a scan-negative cohort. A psychogenic hypothesis for a CES with negative imaging cohort has been postulated, with positive preliminary findings.